A Defect‐Free Principle for Advanced Graphene Cathode of Aluminum‐Ion Battery. Issue 12 (23rd January 2017) - Chen, Hao; Guo, Fan; Liu, Yingjun; Huang, Tieqi; Zheng, Bingna; Ananth, Nimrodh; Xu, Zhen; Gao, Weiwei; Gao, Chao
Abstract : A conceptually new defect‐free principle is proposed for designing graphene cathode of aluminum‐ion battery: the fewer the defects, the better the performances. Developed through scalable approach, defect‐free graphene aerogel cathode affords high capacity of 100 mAh g −1 under an ultrahigh rate of 500 C, exceeding defective graphene and previous reports. This defect‐free principle can guide us to fabricate better graphene‐based electrodes.